Battle of the hemichannels – Connexins and Pannexins in ischemic brain injury. Issue 45 (October 2015) - Davidson, J.O.; Green, C.R.; Bennet, L.; Gunn, A.J.
Abstract: Perinatal ischemic brain injury can occur as a result of a global ischemic insult or focal ischemic stroke in the preterm or full-term neonate. One of the most striking features of HI injury is that, after initial recovery of cellular oxidative metabolism, there is a delayed, 'secondary' mitochondrial failure that spreads over time from the most severely damaged areas outwards, into previously undamaged regions. This secondary failure is accompanied by transient seizure activity and cytotoxic edema. The specific mechanisms of this spread are poorly understood, but it is at least partly associated with spreading waves of depression that can trigger cell death in neighboring uninjured tissues. Both Connexin and Pannexin hemichannels may mediate release of paracrine molecules that in turn propagate cell death messages by releasing intracellular mediators, such as ATP, NAD +, or glutamate or by abnormally prolonged opening to allow cell edema. This review will discuss the controversy around the relative contribution of both Connexin and Pannexin hemichannels and mechanisms by which they may contribute to the spread of ischemic brain injury.